Assessment of Knowledge of Gingival Disease among the Patients attending Kantipur Dental College, Kathmandu - Khanal, Sunita; Bhattarai, Rosina; Dhami, Bhageshwar; Rao, G. Nagaraja; Shrestha, Sujita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: According to the National pathfinder survey of Nepal 2004, gingival disease is one of the most common oral diseases and if left untreated may lead to tooth loss. Aim: To assess the knowledge of gingival diseases among the patients attending Kantipur Dental College, Kathmandu. Materials and Methods: A cross sectional study was conducted among the patients attending Kantipur Dental College. The study was conducted from July to September 2016 with a sample size of 255. A specially designed questionnaire was used for data collection and SPSS version 20 was used for data analysis. Results: Out of 255 participants, males were 127 in number and females 128. The questionnaire consisted of three domains and it was found that 67.1% had fair knowledge on basic knowledge of gingival diseases, 52.2% had fair knowledge on the etiology of disease and 52.2% had good knowledge on the treatment of gum diseases. While applying chi-square test, age and knowledge on all the three domains of disease were statistically significant whereas gender and knowledge were statistically insignificant. Conclusion: This study showed that the level of knowledge among the studied population regarding gingival diseases was fair.